Sport and Medicine - Blonstein, J L (1966)
Dr J L Blonstein spoke of the medical aspects of amateur boxing, and showed that serious injuries are comparatively rare and that the accident rate compares very favourably with those of other sports. He went on to outline the various boxing injuries and their treatment. Dr A L Bass surveyed the treatment and rehabilitation of football injuries, most of which are concerned with soft tissue trauma. He emphasized the importance, to a professional footballer, of returning to activity in a fully recovered state and outlined the facilities which are necessary to ensure this. Dr Roger Bannister considered physiological mechanisms involved in athletic performances and factors affecting transport of oxygen to the muscles.